Issues and Prospects of Poultry Industry Development in Kazakhstan - YESBOLOVA, Ainur Y.; MERGENBAEVA, Aziza T.; ABDIKERIMOVA, Gulzhanar I.; KYDYROVA, Zhamilya Sh.; KUNAFINA, Gulzhan T.; MACIEJCZAK, Mariusz (Journal of Advanced Research in Law and Economics; Vol 7 No 3 (2016): JARLE, Volume VII, Issue 3(17), Summer 2016, 2016)
The paper provides coherent description of the poultry sector in Kazakhstan. By using multiple-factor analysis, the authors aimed at forecasting possible development of this industry in the mid-term perspective. Additionally, based on the foresight investigation, the study suggests institutional measures that would enhance the development and competitiveness of the Kazakh poultry industry as a supply chain based on integrated platform. The study generally shows that poultry industry in Kazakhstan is one of the most perspective branches of agrifood sector, characterized by growth potential and competitiveness possibility in the world market. It is argued however, that although the governmental policy focuses on the technical and market factors, which are crucial for further development; future prospects of this sector imply its supply chain orientation.